IMPLEMENTASI PROGRAM SHOLAT DUHA SETIAP PAGI DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK SD NEGERI 102/X LAMBUR I - Deka Saputra; Jajang Kurniawan; Risdaliani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of the daily Duha prayer program in shaping the religious character of elementary school students. This research employed a qualitative approach using a case study method conducted at SD Negeri 102/X Lambur I. The research subjects consisted of the principal, classroom teachers, Islamic Religious Education teachers, and students. Data were collected through observation, in-depth interviews, and documentation, while data analysis was carried out through data reduction, data display, and conclusion drawing. The results indicate that the daily Duha prayer program has been implemented regularly and systematically as part of the school culture. The implementation of this program has a positive impact on the formation of students’ religious character, particularly in improving discipline, responsibility, inner calmness, and awareness of worship. The success of the program is supported by teachers’ role modeling and the principal’s support, although several technical obstacles were still found during its implementation. Overall, the daily Duha prayer program is effective as a form of worship habituation in strengthening the religious character of elementary school students.